131. Antiviral NL-CVX1 Efficiently Blocks Infection of SARS-CoV-2 Viral Variants of Concern (VOC). (4th December 2021) - Su, Wen; Walker, Matthew; Rebelo, Maria; Tang, Cong; Coelho, Ana R; Tatalick, Laurie; Riley, Marianne; Yu, Kevin; Blancas-Mejia, Luis M; Silva, Daniel-Adriano; Shoultz, David; Bernardes, Goncalo; et al.
Abstract: Background: Using a computational approach, NL-CVX1 was developed by Neoleukin Therapeutics, Inc. to create a de novo protein that both blocks SARS-CoV-2 infection and is highly resilient to viral escape. In this study we evaluated the efficacy of NL-CVX1 against variants of the original SARS-CoV-2 strain, including important viral variants of concern (VOC) such as B.1.1.7, B.1.351, and P.1. Methods: The relative binding affinity of NL-CVX1 to the SARS-CoV-2 viral spike protein of VOC was measured using biolayer interferometry (Octet). A competitive ELISA measured the ability of NL-CVX1 to compete with hACE2 for binding to the receptor binding domain (RBD) of the SARS-CoV-2 S protein from the original strain and VOC. The activity of NL-CVX1 in preventing viral infection was assessed by evaluating the cytopathic effects (CPE) of SARS-CoV-2 in a transmembrane protease, serine 2-expressing Vero E6 cell line (Vero E6/TMPRSS2) and determining the viral load using quantitative real-time reverse transcriptase polymerase chain reaction in infected cells. A K18hACE2 mouse model of SARS CoV-2 infection was used to study the dose-response of NL-CVX1 anti-viral activity in vivo . Results: NL-CVX1 binds the RBD of different VOC of SARS-CoV-2 at low nanomolar concentrations (Fig 1; Kd < 1- 5 nM). When competing with hACE2, NL-CVX1 achieved 100% inhibition against hACE2 binding to the RBD of different VOC with IC50s values ranging from 0.7-53 nM (Fig 2). NL-CVX1 neutralized the B.1.1.7 variant as efficiently as the original strain in Vero E6/TMPRSS2 cells, with EC50 values of 16 nM and 101.2 nM, respectively (Fig 3). In mice, we found that a single intranasal dose of 100 µg NL-CVX1 prevented clinically significant SARS-CoV-2 infection and protected mice from succumbing to infection. Results from additional in vitro and in vivo experiments to be conducted this summer will be presented. Figure 1. NL-CVX1 binds the RBD from multiple strains of SARS-CoV-2 at low nanomolar concentrations. Figure 2. NL-CVX1 achieves 100% inhibition against all strains tested, including SARS-CoV-2 VOC. Figure 3. NL-CVX1 neutralizes the B.1.1.7 variant as efficiently as the original SARS-CoV-2 strain. Conclusion: In vitro and in vivo data (Fig 4) demonstrate that NL-CVX1 is a promising drug candidate for the prevention and treatment of COVID-19. As a hACE2 mimetic, it is resilient to antibody escape mutations found in SARS-CoV-2 VOC. NL-CVX1 further demonstrates the power and utility of de novo protein design for developing proteins as human therapeutics. Figure 4. NL-CVX1 is effective in preventing clinically significant SARS-CoV-2 viral infection in a K18hACE2 mouse model. Disclosures: Matthew Walker, PhD, Neoleukin Therapeutics, Inc. (Employee, Other Financial or Material Support, Ownership options and stock.) Laurie Tatalick, DVM, PhD, DACVP, Neoleukin Therapeutics, Inc. (Consultant, Other Financial or Material Support, Ownership options and stock.) Marianne Riley, BS, Neoleukin Therapeutics, Inc. (Employee, Other Financial or Material Support, Ownership options and stock.) Kevin Yu, BS, MS, Neoleukin Therapeutics, Inc. (Employee, Other Financial or Material Support, Ownership options and stock.) Luis M. Blancas-Mejia, PhD, Neoleukin Therapeutics, Inc. (Employee, Other Financial or Material Support, Ownership options and stock.) Daniel-Adriano Silva, PhD, Neoleukin Therapeutics, Inc. (Advisor or Review Panel member, Other Financial or Material Support, Ownership of Neoleukin options and stock) David Shoultz, PhD, MBA, Neoleukin Therapeutics, Inc. (Employee, Other Financial or Material Support, Ownership options and stock.) Goncalo Bernardes, PhD, Neoleukin Therapeutics, Inc. (Consultant, Advisor or Review Panel member, Shareholder) Hui-Ling Yen, PhD, Neoleukin Therapeutics, Inc. (Grant/Research Support)Saiba AG (Other Financial or Material Support, Received donation from Saiba AG)